2013
DOI: 10.1128/jb.01103-13
|View full text |Cite
|
Sign up to set email alerts
|

 K of Clostridium acetobutylicum Is the First Known Sporulation-Specific Sigma Factor with Two Developmentally Separated Roles, One Early and One Late in Sporulation

Abstract: e Sporulation in the model endospore-forming organism Bacillus subtilis proceeds via the sequential and stage-specific activation of the sporulation-specific sigma factors, H (early), F , E , G , and K (late). Here we show that the Clostridium acetobutylicum K acts both early, prior to Spo0A expression, and late, past G activation, thus departing from the B. subtilis model. The C. acetobutylicum sigK deletion (⌬sigK) mutant was unable to sporulate, and solventogenesis, the characteristic stationary-phase pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 60 publications
1
65
1
Order By: Relevance
“…Surprisingly, disruption of sigK in C. difficile did not lead to the complete loss of sporulation, as 10 3 heat-resistant spores/ml were detected at 72 h (25,94). This finding is in stark contrast to the sigK mutants generated in B. subtilis, C. perfringens, C. botulinum, and C. acetobutylicum, all of which resulted in an asporogenous phenotype (37,63,64,66). TEM image analysis revealed that the C. difficile sigK mutant produced forespores with what appears to be a cortex layer, but no coat layer was observed (94) (Fig.…”
Section: K Has a Second Role Late In Sporulation As The Second Mothcontrasting
confidence: 51%
See 4 more Smart Citations
“…Surprisingly, disruption of sigK in C. difficile did not lead to the complete loss of sporulation, as 10 3 heat-resistant spores/ml were detected at 72 h (25,94). This finding is in stark contrast to the sigK mutants generated in B. subtilis, C. perfringens, C. botulinum, and C. acetobutylicum, all of which resulted in an asporogenous phenotype (37,63,64,66). TEM image analysis revealed that the C. difficile sigK mutant produced forespores with what appears to be a cortex layer, but no coat layer was observed (94) (Fig.…”
Section: K Has a Second Role Late In Sporulation As The Second Mothcontrasting
confidence: 51%
“…TEM image analysis (Fig. 5) showed that these cells proceeded to a more advanced stage of spore morphogenesis than did cells of the C. acetobutylicum sigG disruption mutant (26) and appeared to be releasing an immature or severely underdeveloped forespore (66). These findings demonstrate that K plays a critical role in late sporulation as well as in very early sporulation prior to Spo0A activation, as supported by the nonsporulating phenotype of the ⌬sigK(p94Spo0A) strain.…”
Section: K Has a Second Role Late In Sporulation As The Second Mothmentioning
confidence: 49%
See 3 more Smart Citations